EVALUATION OF PHARMACOLOGICAL ACTIVITIES OF PIPER BETLE L. EXTRACT ON BACTERIAL CONJUNCTIVITIS MODEL OF WISTAR RAT CAUSED BY STREPTOCOCCUS PNEUMONIAE - Pratama, Yudhi; Aldy, Fithria (Majalah Oftalmologi Indonesia, 2023)
Introduction: Conjunctivitis is an eye infection accounted as the third leading ophthalmology cases after cataract and glaucoma globally, with Streptococcus pneumoniae as the main causes in children. Several studies had indicated that Piper betle L. extract inhibited Streptococcus pneumoniae growth. Methods: This study was an analytical study with true experimental design and pre-test-post-test control group. Streptococcus pneumoniae colony growth media was analyzed using Mueller Hinton agar.  Streptococcus pneumoniae colony was calculated using Total Plate Count methods. Results: Sample of this study involved 30 male wistar rat aged 4 – 9 minggu. Kruskal Wallis test reveald a significant differences of Streptococcus pneumoniae colony based on the treatment group (p=0,023). Subsequent test using Posthoc revealed that there was a significant differences in Streptococcus pneumoniae colony between placebo group and group using 25% (p = 0,039) and 30% (p=0,006) piper betle. Test results also revealed that no significant difference was found between placebo group and groups using 20% piper betle (p=0,159) and ofloxacin (p=1,000). Conclusion: There was a significant difference in Streptococcus pneumoniae colony among placebo group and piper betle eyedrops 25 % and 30 % group. However, significant result among placebo group and piper betle L. 20 % and ofloxacin group were absent. Keywords: Bacterial conjungtivitis, Streptococcus pneumoniae, Piper betle L.